THE EFFECTIVENESS OF BILINGUAL THEMATIC MODULE BASED TOWARD STUDENTS LEARNING ACHIEVMENT - Ina Rohiyatussakinah; Nur Hidayanti (FKIP, Universitas Banten Jaya, 2019)
Thematic learning is being promoted where in one learning is interrelated. The purpose of this study is first, to find out how much students respond to the use of bilingual modules in thematic learning, and to find out how much thematic learning achievement using bilingual modules. This research was conducted at SDIT Widya Cendekia, Serang, Banten, using quantitative writers. The writers used a bilingual module on thematic learning therefore students were more interested and easier to learn. The activities of students who pay attention to the lessons explained by the teacher was still a few, therefore the subject matter delivered is poorly understood by students. Used of bilingual modules is one alternative that can be used thematic concepts it could be better understood by students. Learning media is used a bilingual module. In general students stated that they agreed to learn thematic using bilingual modules in class. This can be seen from the student response seen from the results of the questionnaire that as many as 77.1% of students gave a high response and 22.9% of students gave a low response. This means that bilingual modules are very effective in learning and their achievement.